PANGERAN DIPONEGORO: The Effectiveness Of Achieving 100% UHC In The City Of Semarang Through Public Service Innovation - Eka Suryawijaya, Tito Wira; Trenandi, Tendi; Jatmiko, Andreas; Safitri, Maria (Journal of Governance and Public Affairs, 2024)
Health services play an important role in people's lives and are the basic right of every individual. Equal and quality access to health services is crucial for people's welfare. This study aims to analyze the effectiveness of public service innovation in achieving 100% UHC in Semarang City, with a focus on PANGERAN DIPONEGORO’s inspirational contribution, in order to provide insight regarding the implementation of the health insurance program and its impact on UHC. The method used in this research is qualitative using the Double Diamond approach with primary data collection through documentation and innovation supporting literature studies and secondary data collection through literature studies and Focus Group Discussions. The results of the study show that the "PANGERAN DIPONEGORO" innovation succeeded in having a significant positive impact in achieving Universal Health Coverage (UHC) in Semarang City. There has been an increase in community participation, accessibility and quality of health services, as well as a competitive advantage that is rarely possessed by other agencies. There have been many studies using public service objects. However, little has been discussed about the contribution and innovation of public services, especially those that focus on the health sector